“AN ANALYTICAL STUDY OF CONSUMERS RELATED SALES PROMOTION IN FMCG” - DHIRAJ KUMAR MISHRA Dr. K. K. Pathak (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
FMCG (Fast Moving Consumer Goods) are those goods which are of low costs, doesn’t need a lot of time, thought and money to purchase and have a relatively quick shelf turnover.The profit margins on each individual FMCG is relatively less. Thus, the profits receive from the FMCG products always calculated on the basis of number of FMCG products sold. Under marketing mix, promotion is one of its pillar and similarly under promotion, sales promotion is one of its pillar. In this study with regard to consumer related sales promotion there are few narrated storiesas projective theory and as operant conditioning theory.This study includes the data collection and data analysis. Data has been collected through survey method from 100 respondents selected through simple random sampling. Help of structured questionnaire was taken for conducting survey. As a part of study, certain theoretical aspects have also been included based on secondary sources.Result of this study focuses on the behaviour of consumers towards sales